2020
DOI: 10.5121/ijcsit.2020.12303
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Learning In Periods of Crisis: Reflections on the Impact of Covid-19

Abstract: Education systems and its actors are generally responding to quarantine and large-scale shutdown (partial) of cities with a sudden shift to Web-Based Learning. However, given that a pandemic of this nature and scale is novel, there is a knowledge gap as to how teachers and learners should respond to the shift, and what the likely impact and the key considerations should be. This study aims to extrapolate and theorize from the existing knowledgebase about the use of Web-Based Learning, as well as from an expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…Another reason for these results could be that the teachers lack digital literacy skills and not using web 2.0 technologies. Chiemeke and Imafidor (2020) stated that teachers feel unprepared for the transition to online learning and implementation. Almanthari et al (2020) stated in their study that the students lacking information about online learning environments are an important obstacle.…”
Section: Resultsmentioning
confidence: 99%
“…Another reason for these results could be that the teachers lack digital literacy skills and not using web 2.0 technologies. Chiemeke and Imafidor (2020) stated that teachers feel unprepared for the transition to online learning and implementation. Almanthari et al (2020) stated in their study that the students lacking information about online learning environments are an important obstacle.…”
Section: Resultsmentioning
confidence: 99%
“…When other studies are examined; In the study he conducted in Ekiz (2020), he examined teachers' evaluations in terms of receiving education about distance education before and, if they did, in terms of efficiency and inefficiency; It has been observed that the number of teachers who receive training is higher than those who do not, but those who consider it inefficient are higher than those who give the efficient answer. Flack et al (2020) stated in their study that the lack of self-confidence of teachers in using technology in the distance education process causes problems, while another study argues that teachers are unprepared for the transition to distance education (Chiemeke & Imafidor, 2020). In another study examining teachers 'readiness for distance education, they evaluated teachers' readiness and self-confidence as a medium level (Üstün et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In line with increasing publication and cited documents in 2021. It is also known that the research on AbL and WbL tends to be more attractive to researchers nowadays [79][80].…”
Section: Comparison Of the Distribution Of Abl And Wbl Publicationsmentioning
confidence: 99%